2016
DOI: 10.1017/rdc.2016.61
|View full text |Cite
|
Sign up to set email alerts
|

Informing Conservation: Towards 14C Wiggle-Matching of Short Tree-Ring Sequences from Medieval Buildings in England

Abstract: This study tested whether accurate dating by AMS radiocarbon wiggle-matching short tree-ring series (c. 30 annual rings) in the medieval period could be achieved., Scientific dating plays a central role in the conservation of historic buildings in England. Precise dating helps assess the significance of particular buildings or elements of their fabric, thus allowing us to make informed decisions about their repair and protection. Consequently considerable weight, both financial and legal, can be attached to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…( B ). OxA data on other known age NH tree rings ( 61 , 62 ) versus IntCal13 ( 1 ). ( C ) Overall 14 C years offset OxA NH data in B versus IntCal13; light gray region shows the neutral prior (0 ± 20) versus the calculated posterior region (blue) ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…( B ). OxA data on other known age NH tree rings ( 61 , 62 ) versus IntCal13 ( 1 ). ( C ) Overall 14 C years offset OxA NH data in B versus IntCal13; light gray region shows the neutral prior (0 ± 20) versus the calculated posterior region (blue) ( 27 ).…”
Section: Resultsmentioning
confidence: 99%
“…The wider envelope on the SHCal13-NEW curve means that when calibrating a radiocarbon determination against it, the credible range for the object's unknown age will generally be wider than the interval obtained by calibrating against SHCal13-RWM, the latter we consider unrealistically precise. Since Bayliss et al (2017) demonstrated that the calendar age range intervals obtained using SHCal13-RWM can be too narrow and provide overly-precise calibration in places, the wider SHCal13-NEW will hopefully provide better calibration accuracy and credible age range coverage.…”
Section: Example 1: Recreating Shcal13mentioning
confidence: 99%
“…Furthermore, because both Galimerti et al (2004) and Goslar and Madry (1998) relied on data simulated from the calibration curve, their studies had no potential for identifying any of the issues that may arise in empirical data. The importance of this empirical evaluation becomes clear once we consider the very recent study of the performance of short-span wiggle-matches in the context of medieval buildings in England (Bayliss et al 2017). Within this study three out of the five dated sequences failed to reproduce the known dendrochronological date for the felling of the timbers.…”
Section: Introductionmentioning
confidence: 99%